2015
DOI: 10.1007/s00264-015-2677-y
|View full text |Cite
|
Sign up to set email alerts
|

Treatment analysis of paediatric femoral neck fractures: a prospective multicenter theraupetic study in Indian scenario

Abstract: Early surgical intervention hastens recovery, rehabilitation and return to school and decreases the risk of developing avascular necrosis. We suggest Smooth Pins fixation in zones I and II (nearer to zone I) and cancellous screw fixation in zones II, III and IV. Decompression of hip joint by capsulotomy releases the tamponade effect and should be performed in all cases of paediatric femoral neck fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…Some authors have found decreased complication rates following open reduction when compared to closed reduction, and recommend open reduction for all pediatric hip fractures. 13 , 14 However, there remains no consensus in the literature as others have shown equivocal results with open and closed methods. 2 , 8 , 12 Open reduction of the hip fracture is required if an acceptable reduction cannot be achieved by closed means or if the fracture is associated with an underlying vascular injury.…”
Section: Reduction Techniquementioning
confidence: 99%
“…Some authors have found decreased complication rates following open reduction when compared to closed reduction, and recommend open reduction for all pediatric hip fractures. 13 , 14 However, there remains no consensus in the literature as others have shown equivocal results with open and closed methods. 2 , 8 , 12 Open reduction of the hip fracture is required if an acceptable reduction cannot be achieved by closed means or if the fracture is associated with an underlying vascular injury.…”
Section: Reduction Techniquementioning
confidence: 99%
“…One 7 years old patient had 4 K-wires in her epiphysis and a total of 6 cannulated screws passed through the physis in 3 operated patients who had a mean age of 15 years old and none had noticeable premature physeal closure or AVN. In a recent prospective multi-center study in Indian population, 28 patients with femoral neck fractures were treated and the authors reported 14.2 % AVN rate with 82.1 % good results according to Ratliff's criteria [23]. In the same study, authors divided femoral neck into four zones and recommended smooth pins near to physis and cancellous screws in zones far to physis [23].…”
Section: Resultsmentioning
confidence: 99%
“…In patients with nondisplaced femoral neck fractures, hematoma will not increase to a size within the capsule that disrupts the blood supply to the femoral head, and in displaced femoral neck fractures, the tearing of the capsule reduces the capsule internal pressure. Panigrahi et al [20] suggested that decompression of the hip joint by capsulotomy releases the tamponade effect and should be performed in all cases of pediatric femoral neck fractures. However, Spence et al [21] reported that the capsular decompression procedure was not predictive of osteonecrosis after pediatric femur fractures.…”
Section: Discussionmentioning
confidence: 99%